Annular Apertures in Point Spread Function of Amplitude Anodization Filters in Peripheral Obscuration - REDDY, G SUDHAAMSH MOHAN (International Journal of Control and Automation, 2019)
In this article the importance of investigating the Point Spread Function (PSF) of an optical system with annular apertures is too well-known to need any introduction. In the present study, we have considered an annular aperture in which the central part is clear and the outer region is apodized with a pair of complimentary filters. The results obtained have been presented graphically and in tabular forms.